A Convenient Synthesis of Gimeracil. (January 2018) - Li, Xiao-lin; Zhu, Hao-ting; Zhan, Li; Liu, Ting; Cheng, Guang; Liu, Ning; Yu, Shan-bao; Li, Hui; Luo, Yu; Yang, Fan; Tang, Jie
A practical three-step synthetic approach to gimeracil in a 68% overall yield is described, using 2, 4-dimethoxypyridine as the starting material with 3, 5-dichloro-2, 4-dimethoxypyridine and 3, 5-dichloro-2, 4-dihydroxypyridine as intermediates. The advantages of this procedure include short reaction steps, simple operation and good yield.